SECTORAL PRIORITIES FOR CONSTRUCTION ACTIVITIES IN UKRAINE - Sergiy Zapototsciy; Victoria Zapototsca; Anna Ekezli (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
This paper considers the theoretical, methodological and applied principles of construction activity. Was made analysis of factors influencing demand and stimulate residential construction, construction of non-residential buildings and engineering structures. Among the stimulating factors analyzed income levels of people and mortgage terms. Evaluation of construction of non-residential buildings and engineering structures includes an analysis of the economy of Ukraine, business development, investment opportunities in the state and commercial structures. Were established and outlined the factors of constraints of building in the context of the studied areas.